Adherence to COVID-19 preventive measures and its association with intimate partner violence among women in informal settings of Kampala, Uganda - Ronald Anguzu; Allen Kabagenyi; Laura D. Cassidy; Simon Kasasa; Abdul R. Shour; Bernadette N. Musoke; Joan N. Mutyoba (Public Library of Science (PLoS), 2022)
Cases of coronavirus disease 2019 (COVID-19) detected, and COVID-19 associated mortality increased since the first case was confirmed in Uganda. While adherence to WHO-recommended measures to disrupt COVID-19 transmission has since been implemented, it has been reported to be sub-optimal. An increase in intimate partner violence (IPV) cases was linked to enforcement of COVID-19 lockdowns and other preventive measures especially in informal settings of Kampala. We determined the association between adherence to COVID-19 preventive measures and intimate partner violence among women dwelling in informal settings in Kampala, Uganda. Between July and October 2020, we conducted a three-month prospective cohort study of 148 women living in informal settlements of Kampala during the COVID-19 lockdown and easing of restrictive measures. Participants were surveyed at baseline, at 3-weeks and 6-weeks (endline). The dependent variable was adherence to COVID-19 preventive measures (remained adherent vs poorly adherent) between baseline and endline surveys. This composite outcome variable was computed from implementing all four variables: social distancing, wearing face masks, frequent hand washing and use of hand sanitizers at baseline and endline surveys. The key independent variable was IPV measured as experiencing at least one form of physical, emotional, or sexual IPV. Covariates were age, education, marital status, household size, occupation, and having problems getting food. Adjusted logistic regression analyses tested the independent association between adherence to COVID-19 preventive measures and intimate partner violence. Among 148 respondents, the mean age (SD) was 32.9 (9.3) years, 58.1% were exposed to at least one form of IPV, and 78.2% had problems getting food. Overall, 10.1% were poorly adherent to COVID-19 preventive measures during the first COVID-19 wave. After controlling for potential confounders, remaining adherent to COVID-19 preventive measures were more likely to experience intimate partner violence when compared to women who were poorly adherent to COVID-19 preventive measures during the first COVID-19 wave in Uganda [OR 3.87 95%CI (1.09, 13.79)]. Proportions of women in informal settlements of Kampala experiencing at least one form of IPV during the first COVID-19 wave is substantial. Remaining adherent to preventive measures for COVID-19 transmission may increase IPV exposure risk among women living in informal settlements in Kampala. Contextualizing COVID-19 interventions to the needs of marginalized and vulnerable women and girls in informal settings of Kampala is warranted. Processes to integrated violence prevention and response strategies into the Uganda COVID-19 prevention strategy are underscored.